Resistances to Gender Mainstreaming: An Analysis of the Trend of Women Engagement in Participatory Gender-Responsive Budgeting in Bangladesh - Shuvra Chowdhury (Journal of Contemporary Governance and Public Policy, 2020)
Gender Responsive budgeting (GRB) is among a few approaches for gender mainstreaming that has been introduced by the governments around the world or international funding organizations to institutionalize gender equality in public reforms. The formal processes of planning and budgeting at the Union Parishad (UP) - the lowest administrative tier of Bangladesh- offer general citizens to raise their demands at the local level. Besides, there is a provision that a 30% fund will be earmarked for women. In this paper, the case of UP gender budgeting practice was analyzed from a gender perspective. On the basis of case oriented qualitative research strategy, this was an empirical study of 06 (six) UPs of three different districts of Bangladesh. The data of this study indicated that members of the Non-Government Organizations (NGO) played a catalyst role in enhancing the access of women in the UP planning and budgeting processes. Along with the existing problems of local-level planning, lack of fiscal decentralization including resource constraint, absence of women development funding, the absence of women administrative officers at the different layers of government offices and obstacles and resistances in religion and patriarchal dimensions are inhibiting women to participate in the participatory processes. For implementing the GRB reform agenda suggestions are made for creating independent women budget groups at the local government level and researching on a broader perspective on GRB issues at the central government level.